Dosimetry measurements using Timepix in mixed radiation fields induced by heavy ions; comparison with standard dosimetry methods. (March 2014) - Ploc, Ondrej; Kubancak, Jan; Sihver, Lembit; Uchihori, Yukio; Jakubek, Jan; Ambrozova, Iva; Molokanov, Alexander; Pinsky, Lawrence
Abstract : Objective of our research was to explore capabilities of Timepix for its use as a single dosemeter and LET spectrometer in mixed radiation fields created by heavy ions. We exposed it to radiation field (i) at heavy ion beams at HIMAC, Chiba, Japan, (ii) in the CERN's high-energy reference field (CERF) facility at Geneva, France/Switzerland, (iii) in the exposure room of the proton therapy laboratory at JINR, Dubna, Russia, and (iv) onboard aircraft. We compared the absolute values of dosimetric quantities obtained with Timepix and with other dosemeters and spectrometers like tissue-equivalent proportional counter (TEPC) Hawk, silicon detector Liulin, and track-etched detectors (TEDs).